Supersonic gas flow for preparation of ultrafine silicon powders and mechanochemical synthesis - Tao, Yang (R Soc Open Sci, 2018)
We report the supersonic gas flow for crush and mechanochemical synthesis. The key instrument parameters for production of supersonic particle flow, such as annular nozzle, expansion angle and length of the accelerating duct, are theoretically designed and optimized. Based on the theoretical results, supersonic gas flow equipment is fabricated. The capacity of the present equipment for production of supersonic particle flow is demonstrated by particle image velocimetry measurement, and the maximum transient velocity of the particles achieves as much as 550 m s(−1). Additionally, the present equipment is applied for continuous and physical preparation of ultrafine Si powders with a high scalability and mechanochemical synthesis of TiO(2) and TiN(x) nanopowders at a high production rate.